Correction to: Recurrence with pagetoid spread arising 17 years after surgery for intramucosal rectal cancer: a case report - Taichi Matsubara; Yuta Kasagi; Kippei Ogaki; Yu Nakaji; Ryota Nakanishi; Yuichiro Nakashima; Masahiko Sugiyama; Hideto Sonoda; Hiroshi Saeki; Eiji Oki; Yoshihiko Maehara (Surgical Case Reports)
Abstract After publication of the original article [1] the authors noted that the following errors had occurred: